THE IMPORTANCE OF FEMALE JUDGES IN ENSURING A FAIR TRIAL (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores the decisive role of female judges in ensuring justice in judicial systems around the world. By carefully analyzing the literature and examining empirical evidence, this study highlights the unique contribution female judges make to lawsuits and outcomes. The findings highlight the importance of gender diversity in the protection of justice, inclusivity, and human rights. In addition, this article provides recommendations for increasing gender equality in judicial appointments to increase the effectiveness and legality of legal systems globally.